Content distribution system based on segmented network coding - Li-Yong Ren; Hai-Ying He; Zhao Di; Ming Lei (2009 International Conference on Apperceiving Computing and Intelligence Analysis, 2009)
The network communication applying network coding, in which the intermediate peers firstly encode the information from source, and then forward the encoded data which will be decoded by the destination peers where the original information gets restored. Previous methods indicate that we can improve throughput and stability of a network, fasten the expanding-velocity of copies, and reduce the download time. Although network coding technology is developing so fast, the critical issue is still how to promote encoding and decoding rates and to decrease the complexity, on which we focus in the field. In this paper, we propose an approach based on segmented network coding which is applied to P2P Content Distribution System (P2PCDS). We implement a P2PCDS based on segmented network coding. Through the experiment, we choose the number of encoding data as a seed, and make a comparison between the P2PCDS with and without network coding in term of average download time and in the resist of churn. The resist of churn in our system is raised by 12.5% and it also shortens average download time. And the experiment shows it's better to adapt P2PCDS under the active Mesh network architecture.